RELEVANCE OF INDICATORS OF SOCIAL EMOTIONAL HEALTH IN DIFFERENT SAMPLES OF ADOLESCENCE - Čukna, Laura; Svence, Guna; Pakse, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this research was to determine whether there are statistically relevant differences in Michael J. Furlong's concept of socio-emotional health with meta construct Covitality (SEV factor) between teenage and youth selections, gender, and nationalities in different schools.The participants of the research were 593 respondents from Latvia, aged 11-19 years. Out of the total selection of participants (N=593) there were 318 teens (M=13.01, SD=.84), of them 151 boys and 167 girls; the other group of 274 young people (M=15.85, SD = 1.02), consisted of 132 males and 142 females. To measure the positive aspects of the mental health, A Socio-emotional Health Survey was used (Social Emotional Health Survey – Secondary, SEHS-S, Furlong, You, Renshaw, & O’Malley; 2014; adapted in Latvian by Kņaze, 2017).There were raised 6 questions in the beginning of the research. Results showed higher results for girls on the scale Belief in Others (its substructure Peer Support) and on the scale Emotional Competence (its substructure Empathy), compared to the selection of boys.The results on the scale Engaged living were statistically higher for teens compared to the selection of the youth. Teens also had higher statistical results of Co-vitality compared to the youth. However, the selection of youth showed statistically higher results in the Emotion Regulation (the substructure of Emotional Competence) compared to the selection of teens.The respondents from city schools showed statistically higher results on the scale Belief in Self, Engaged Living and Co-vitality compared to students from town schools. The Regression Analysis highlights the importance of the school environment in Co-vitality, which explains the 3% variance of the socio-emotional health.